Pengaruh Kepemimpinan Transformasional dan Budaya Organisasi terhadap Workplace Learning dan Perilaku Kerja Inovatif Pegawai pada Badan Perencanaan Pembangunan dan Penelitian Pengembangan Daerah Kabupaten Barito Timur - LINDA SUSANTI (JURNAL KINDAI, 2023)
Abstract : This study aims to determine and analyze the influence of transformational leadership and organizational culture on workplace learning and transformational leadership and organizational culture on innovative work behavior of employees at the Regional Development Planning and Research Agency for East Barito Regency. This study uses the census method. The sample used in this study was 40 respondents, where data was collected through questionnaires distributed. The analysis is based on respondents' answers obtained through questionnaires distributed by researchers. The data analysis technique used partial least squares (PLS) structural equation model (SEM) analysis with the SmartPLS 3.2.0 program. The results of research on 40 employees at the Development Planning Agency and Regional Development Research in East Barito Regency showed that 1) transformational leadership has a positive and significant effect on workplace learning as evidenced by the significance value. 2) organizational culture has a positive and significant effect on workplace learning. 3) Transformational leadership has a positive and significant effect on employee innovative work behavior. 4) Organizational culture has a positive and significant effect on employee innovative work behavior and 5) Workplace learning has a positive and significant effect on employee innovative work behavior at the Regional Development Planning and Research Agency for East Barito Regency Keywords: Transformational Leadership, Organizational Culture, Workplace Learning, Innovative Work Behavior